Constraining the kinematics of metropolitan Los Angeles faults with a slip‐partitioning model - Daout, S. (2018)
Due to the limited resolution at depth of geodetic and other geophysical data, the geometry and the loading rate of the ramp‐décollement faults below the metropolitan Los Angeles are poorly understood. Here we complement these data by assuming conservation of motion across the Big Bend of the San Andreas Fault. Using a Bayesian approach, we constrain the geometry of the ramp‐décollement system from the Mojave block to Los Angeles and propose a partitioning of the convergence with 25.5 ± 0.5 mm/yr and 3.1 ± 0.6 mm/yr of strike‐slip motion along the San Andreas Fault and the Whittier Fault, with 2.7 ± 0.9 mm/yr and 2.5 ± 1.0 mm/yr of updip movement along the Sierra Madre and the Puente Hills thrusts. Incorporating conservation of motion in geodetic models of strain accumulation reduces the number of free parameters and constitutes a useful methodology to estimate the tectonic loading and seismic potential of buried fault networks.